PENGARUH PENGGUNAAN LKPD BERBASIS DEEP LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Ridho Firmansyah, Rahmat; Faridah, Luluk; Nurul Aini, Khafidhoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical problem-solving ability is one of the essential competencies that students need to develop in mathematics learning; however, this ability has remained relatively low. One effort to improve students' mathematical problem-solving ability was through the use of Deep Learning-based Student Worksheets (LKPD). This study aimed to determine the effect of Deep Learning-based LKPD on senior high school students’ mathematical problem-solving ability in quadratic function material. The study employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 60 students divided into an experimental class and a control class. The research instruments included a Deep Learning Lesson Plan (RPM) and a mathematical problem-solving test that had met validity and reliability criteria. The data were analyzed using N-Gain, normality tests, homogeneity tests, and an Independent Sample t-Test with IBM SPSS Statistics. The results show that the average N-Gain score of the experimental class is 0.6313, while that of the control class is 0.3641. The hypothesis testing result indicates a significance value (2-tailed) of < 0.001, indicating a significant difference between the two groups. Therefore, the use of Deep Learning-based LKPD has a positive effect on students’ mathematical problem-solving ability and serves as an effective alternative teaching material in mathematics learning.